Optimising Soilless Culture Systems and Alternative Growing Media to Current Used Materials - Gruda, Nazim; Fernández, Juan A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book represents a Special Issue collection called: "Optimising Soilless Culture Systems and Alternative Growing Media to Current Used Materials". Nine original papers, one review, and an Editorial from 41 authors from different countries were published in this Special Issue. New strategies and technologies, including new sustainable raw materials, should be continually developed to solve specific cultivation limitations, optimise existing systems, reduce related environmental impacts, and address the impacts of climate change.